Current and emerging anti-angiogenic therapies in gastrointestinal and hepatobiliary cancers - Saoudi González, Nadia; Castet, Florian; Élez, Elena; Macarulla, Teresa; Tabernero, Josep (Frontiers in Oncology, 2022)
Gastrointestinal tumours are a heterogeneous group of neoplasms that arise in the gastrointestinal tract and hepatobiliary system. Their incidence is rising globally and they currently represent the leading cause of cancer-related mortality worldwide. Anti-angiogenic agents have been incorporated into the treatment armamentarium of most of these malignancies and have improved survival outcomes, most notably in colorectal cancer and hepatocellular carcinoma. New treatment combinations with immunotherapies and other agents have led to unprecedented benefits and are revolutionising patient care. In this review, we detail the mechanisms of action of anti-angiogenic agents and the preclinical rationale underlying their combinations with immunotherapies. We review the clinical evidence supporting their use across all gastrointestinal tumours, with a particular emphasis on colorectal cancer and hepatocellular carcinoma. We discuss available biomarkers of response to these therapies and their utility in routine clinical practice. Finally, we summarise ongoing clinical trials in distinct settings and highlight the preclinical rationale supporting novel combinations.